Religiosity, Forgiveness, and Subjective Well-Being Among Adolescents in Yogyakarta - Sutipyo Ru’iya, Ahmad Muhammad Diponegoro, Hanif Cahyo Adi Kistoro (International Journal of Advanced Science and Technology, 2020)
The adolescent is essential in human life. Usually, people who succeed in this period will flourish in their life. One crucial aspect of an adolescent is happiness. Happiness will make someone relax, responsible for his individual experience and his community. This research aims to understand the relationship between religiosity, forgiveness, and subjective well-being. The forgiveness was studied because the adolescents find difficulties to practice forgiveness in his community. This study examines the relationship between Islamic religiosity and forgiveness with subjective well being. Forgiveness was investigated in this study. This research uses a quantitative approach to canonical data analysis. In this study, Respondents were students of class XI at one of the favorite Aliyah State Madrasahs in Yogyakarta. Class XI consists of eight classes with 207 students, then 130 samples were taken proportionally in each class. The results showed that the canonical loading of the dependent variable was 0.869 (life satisfaction) and 0.845 (affect). While, the canonical loading of an independent variable is 0.821 (forgiveness) and 0.756 (Islamic religiosity). From these results, it was concluded that there was a positive and significant mutual relationship between Islamic religiosity and forgiveness with the subjective well-being (satisfaction of life and affect).